Excess Mortality as a Tool to Monitor the Evolution of Health Emergencies: Choices, Challenges, and Future Directions - Paglino, Eugenio; Stokes, Andrew C. (American journal of public health (1971), 2024)
Excess mortality has become one of the most popular metrics to assess the impact of the COVID-19 pandemic across the world. Excess mortality has three key advantages relative to alternatives: (1 ) it requires relatively little data (in the most basic form, a historical time series of annual deaths), (2) it does not depend on whether causes of death are accurately assigned on death certificates, and (3) it can be compared across space and time.